An Engagement Mediates the Influence of Empowerment and Transformational Leadership on Employee Performance - Setioningrum, Vega; Nilasari, B Medina (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2025)
The number of hospitals in Indonesia is experiencing significant growth, especially in profit-oriented private industries. This is because hospitals are very important for the community in obtaining health services, thereby triggering high competition. In response to this competition, good human resource performance is needed. This study aimed to analyze the effect of empowerment, and transformational leadership on employee performance with engagement as a mediating variable. The study was conducted to update previous investigations, by adding employee empowerment variables to hospitals which are expected to provide different results. The sample comprises 237 employees of Harbour Group Hospitals in Indonesia and data were analyzed using SEM analysis with AMOS 23. The results showed that employee empowerment and transformational leadership had a significant influence on performance. Furthermore, employee engagement was proven to mediate empowerment and transformational leadership on performance. The implementation of a transformational leadership style can facilitate bonds between employees, thereby improving performance. Managerial implications are that management offers appropriate support and development opportunities to motivate and maintain high levels of employee performance; management establishes programs to improve leadership, decision-making, and risk management competencies at the managerial level; management provides responsibility and autonomy to employees in their work to increase ownership and involvement